Analysis of Toraja Generation Perspectives on Tongkonan Functions and Values - Linerda Tulaktondok; Judith Ratu Tandi Arrang; Eko Suripto Pasinggi (Teaching English as a Foreign Language Overseas Journal, 2019)
Tongkonan is the life of the Toraja people because that's where all their values ??and aesthetics are. In it there are not only functions as residential houses but there are social functions and power, traditional and cultural values, and religious values. But the passage of time and the development of the modern era as well as the influence of culture from the outside to make a shift and change the function and value of the actual Tongkonan so much to cause conflicts in the family and community. Many perspectives from the Toraja generation emerge. This study aims to identify and describe how the perspective of the older generation and young generation of Toraja on the function and value of Tongkonan. Researchers chose respondents who live in Toraja by snowball. The researcher uses the semi-structured interview as an instrument to obtain data and a qualitative description method in analyzing data. The results showed that the older generation emphasized the view that Tongkonan is a form of parents of one descendant who has a customary life structure that must be followed according to established rules so that if there is a problem returning to pay attention to the rules, and because Tongkonan is the form of parents, the child must dutiful to parents. In addition, the younger generation views Tongkonan as a physical form of a shared house in which there is economic value. There is no significant perspective difference between the two generations on the function and value of tongkonan, both agree and realize the importance of preserving the value and function of the tongkonan. But in general the younger generation is less interested and do not have time to hear the stories of parents / grandparents and so do not have a deep understanding.